THE USE OF ENOXAPARIN IN ACUTE CORONARY SYNDROME - E. A. Smirnova; S. S. Yakushin (Столичная издательская компания, 2017)
The article discusses the choice of anticoagulant in different patterns of acute coronary syndrome (ACS). According to current recommendations three groups of agents are used as anticoagulants in ACS: unfractionated heparin (UFH) and low molecular weight heparin (LMWH), fondaparinux, and bivalirudin. UFH was the main parenteral anticoagulant therapy for ACS for several decades, including percutaneous coronary interventions, but a number of limitations and side effects of the drug contributed to the emergence of new anticoagulants with lower molecular weight. Among the LMWH, which have a higher bioavailability and significant convenience of administration, only enoxaparin has significant clinical advantage over UFH considering the prognosis for patients with ACS. At the same time throughout the period of ACS, including invasive procedures, change of heparin products is extremely undesirable, since switching from enoxaparin to UFH and vice versa, not only reduces the effectiveness of the treatment, but also increases the risk of bleeding. Fondaparinux has optimal efficacy/safety profile in ACS with no ST elevation, regardless of the chosen tactics. If it is unavailable, enoxaparin or UFH may be an alternative. Bivalirudin is the optimal alternative to UFH in combination with GP IIb/IIIa platelet receptor blockers in case of invasive treatment strategy. In patients with impaired renal function with glomerular filtration rate (GFR)<30 mL/min/1.73m2 enoxaparin dose should be reduced to 1 mg/kg, 1 time a day, with GFR <15 mL/min/1.73m2 the drug is contraindicated. Fondaparinux safety is superior to enoxaparin in patients with chronic kidney disease, however the drug is not recommended in GFR<20 ml/min/1.73m2. In this case UFH should be preferred due to the ease of monitoring anticoagulant activity and the ability to quickly neutralize its activity in the case of bleeding.